Baseball in April : and other stories - Soto, Gary. (San Diego : Harcourt Brace, 1990)
A collection of eleven short stories focusing on the everyday adventures of Hispanic young people growing up in Fresno, California. In this unique collection of short stories, the small events of daily life reveal big themes-love and friendship, youth and growing up, success and failure. Calling on his own experiences of growing up in California's Central Valley, poet Gary Soto brings to life the joys and pains of young people everywhere. The smart, tough, vulnerable kids in these stories are Latino, but their dreams and desires belong to all of us. 5-1/8 X 7-5/8.
Broken chain -- Baseball in April -- Two dreamers -- Barbie -- The no-guitar blues -- Seventh grade -- Mother and daughter -- The karate kid -- La bamba -- The marble champ -- Growing up.
Keywords: Children's stories, American; Mexican Americans -- California -- Juvenile fiction; Short stories